THE RELATIONSHIP BETWEEN BODY MASS INDEX (BMI) AND PRE-EKLAMPSIA IN RSIA AMANAT MAKASSAR CITY - Bunayya Hartadi, Andi Yusnita Latifa; M. Said, Masita Fujiko; Khalid, Nur Fadhillah; Hamsah, M.; Royani, Ida (HEARTY, 2025)
The success of maternal health programs is often evaluated using the Maternal Mortality Rate (MMR), which measures deaths during pregnancy, childbirth, and the puerperium due to pregnancy-related causes. In 2020, hypertension in pregnancy was a leading cause of maternal deaths, with 1,110 cases reported. Pre-eclampsia, characterized by hypertension (blood pressure ≥140/90 mmHg) and proteinuria after 20 weeks of gestation, is a significant concern. Overweight and obesity are high-risk factors associated with increased pregnancy complications, including pre-eclampsia. This study aimed to analyze the relationship between Body Mass Index (BMI) and pre-eclampsia at Amanat Hospital in Makassar City. Using an observational analytic design with a cross-sectional approach, 284 pregnant women were assessed. The prevalence of pre-eclampsia was found to be 9.9%, with 28 women diagnosed. Bivariate analysis using the Chi-Square test revealed a significant association between BMI and pre-eclampsia (p = 0.001), while no significant association was found between Upper Arm Circumference (LILA) and pre-eclampsia (p = 0.348). The study concludes that BMI is significantly associated with pre-eclampsia, whereas LILA does not show a significant relationship.